Synthesis, Characterization And Computational Studies Of Novel (E)-N-(3,4-Dimethoxybenzylidene)naphthalen-1-amine - . Mariyam; B. F. Y. Serli; N. Adliani (Journal of Science and Applicative Technology, 2019)
Novel (E)-N-(3,4-dimethoxybenzylidene)naphthalen-1-amine (DBNA) ligand has been synthesized by refluxing 1-naphthylamine and 3,4-dimethoxybenzaldehyde in methanolic solution for 5-6 hours. The obtained compound was characterized by UV-Vis, FT-IR and 1H-NMR. All the spectral data confirmed the structure of the ligand.